THREE DIMENsION MODELLING OF OUTPUT CHARACTERISTICS OF GALLIUM ARSENIDE TRANSISTORS with submicron length of the gate - V. N. Mishchenka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Modeling results of output static characteristics of gallium arsenide transistors for extreme high frequency range are given. Direct ion-implanted gallium arsenide transistors with the special profile under the gate are analyzed. Many particle Monte Carlo method with the solving of the Poisson equation are used for simulation of the three dimension structure with submicron length of the gate. Investigation of the gallium arsenide device provided the new results which connected with the influence of the geometrical size of the structure and features of gate construction to the output static characteristics. New modeling method of contact regions in device is presented for gallium arsenide transistors.